Analysis of microbial diversity in Muscat Hamburg wine and Shine-Muscat wine - Shumin, Yao; Mengqi, Zhang; Mengqi, Zhang; Qike, Yu; Yuxi, Liu (Emirates Journal of Food and Agriculture, 2023)
Different microbes in grapes lead to different flavors of wine. There are many kinds of wine grapes. In this article, the microorganisms in the wine made by the Muscat Hamburg grape and the Shine-Muscat grape are analyzed by using high-throughput sequencing technology. The results indicate that there are 8 species of dominant bacteria phylum which are Bacteroidetes, Firmicutes, Proteobacteria, Actinobacteria, Acidobacteria, Epsilonbacteraeota, Fusobacteria and Chloroflexi , and 13 species of dominant bacteria genus in Muscat Hamburg wine. There are 7 species of dominant bacteria phylum which are Bacteroidetes、Firmicutes、Proteobacteria、Actinobacteria、Acidobacteria、Epsilonbacteraeota、Fusobacteria and 14 species of dominant bacteria genus in Shine-Muscat wine. The dominant fungi phylum of the two varieties of wine are Ascomycota, Basidiomycota and Zygomycota. There are 2 species of dominant fungi genus in Muscat Hamburg wine and 9 species of dominant fungi genus in Shine-Muscat wine. At the genus level, bacteria are more abundant than fungi in the dominant genera of microorganisms in these two varieties of wine, and the diversity at the genus level was higher than that at the phylum level.